2022
DOI: 10.1177/08987564221099133
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Extractions of Deciduous Mandibular Canine Teeth to Correct Linguoversion Malocclusion in 17 Dogs

Abstract: A search of medical records at the Center for Veterinary Dentistry and Oral Surgery, Gaithersburg, MD was conducted to identify patients who received extractions of deciduous mandibular canine teeth to treat linguoversion. Patients were included if they were less than 5.5 months of age and had a diagnosis of deciduous class 2 or bilateral class 1 malocclusions. Treatment was considered a success if normocclusion of the permanent dentition was achieved at follow up evaluation. Seventeen patients represented 13 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Finally, the sample size for this publication was small, though much larger than a comparable study. 13 This study showed that when deciduous LMCs are extracted prior to the eruption of the permanent mandibular canine teeth, most dogs with class 1 malocclusion resulted in a normal permanent occlusion. Furthermore, in this study, individuals treated for permanent LMCs with abnormal soft tissue contact that were diagnosed during the eruption phase were successfully treated by gingivectomy and gingivoplasty.…”
Section: Methodsmentioning
confidence: 78%
See 2 more Smart Citations
“…Finally, the sample size for this publication was small, though much larger than a comparable study. 13 This study showed that when deciduous LMCs are extracted prior to the eruption of the permanent mandibular canine teeth, most dogs with class 1 malocclusion resulted in a normal permanent occlusion. Furthermore, in this study, individuals treated for permanent LMCs with abnormal soft tissue contact that were diagnosed during the eruption phase were successfully treated by gingivectomy and gingivoplasty.…”
Section: Methodsmentioning
confidence: 78%
“…Finally, the sample size for this publication was small, though much larger than a comparable study. 13…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation